2019
DOI: 10.1080/19440049.2019.1583381
|View full text |Cite
|
Sign up to set email alerts
|

Review of micro- and nanoplastic contamination in the food chain

Abstract: Whereas the dramatic environmental impact of plastic waste rightfully receives considerable attention by scientists, policy makers and public in general, the human health impact of microand nanoplastics contamination of our food and beverages remains largely unknown. Indeed, most studies aim at understanding the environmental impact rather than the human health impact of a possible exposure to micro-and nanoplastics. In addition, these papers generally lack a methodological, standardised approach. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
208
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(240 citation statements)
references
References 121 publications
(137 reference statements)
2
208
0
2
Order By: Relevance
“…Given that both mealworms and superworms have also been evaluated to be nutritious as fish feed 20 and poultry 11 , the mealworm and superworm are valuable plastic degraders that can also be used to provide cost-effective feed in food production in urban farming. While further research is required to ensure that plasticizers or other plastic degradation products do not bioaccumulate and get introduced into the food chain to humans (see review on plasticizer accumulation in the food chain 21,22 ), the ability of our frass analysis shows promise for reasonably safe degradation of PS, a finding in agreement with many other reports 8,9,16,17,23 .…”
Section: Discussionsupporting
confidence: 82%
“…Given that both mealworms and superworms have also been evaluated to be nutritious as fish feed 20 and poultry 11 , the mealworm and superworm are valuable plastic degraders that can also be used to provide cost-effective feed in food production in urban farming. While further research is required to ensure that plasticizers or other plastic degradation products do not bioaccumulate and get introduced into the food chain to humans (see review on plasticizer accumulation in the food chain 21,22 ), the ability of our frass analysis shows promise for reasonably safe degradation of PS, a finding in agreement with many other reports 8,9,16,17,23 .…”
Section: Discussionsupporting
confidence: 82%
“…Research priorities should focus on NMPs to get a better understanding of all processes related to the generation, fate, exposure, and effects of those plastics. Recent literature reviews confirmed the presence of MPs in surface water and sediments as well in some (limited) food products (Burns and Boxall 2018;Toussaint et al 2019;Hantoro et al 2019;Koelmans et al 2019 and papers cited herein). Detection and quantification of NMPs in complex matrices such as food products is difficult, primarily due to the absence of reliable analytical methods (Hermsen et al 2018).…”
Section: Researchers' Needs and Expectationssupporting
confidence: 71%
“…Moreover, concerning the impact on human health, it is also important to understand the MP exposure through food and drinking water consumption . Although numerous scientific studies confirm that the highest quantities of MPs are in the digestive tract of seafood, which is a part of commercial fish that is usually discarded before consumption, there is still little knowledge about NMPs in other food products (Toussaint et al 2019). The European Food Safety Authority concluded that there is an urgent need for occurrence data in food and moreover to understand the effects of food processing (EFSA 2016).…”
Section: Researchers' Needs and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, MP has been detected not only in various water bodies [6][7][8], soils and sediments [9][10][11], but also in indoor air [12], table salts [13], and even in the atmosphere in remote areas [14]. More recently, ingestion and entanglement of MP was also found by freshwater and deep-sea organisms [15][16][17][18], which raised a concern that the human food chain is under risk of MP contamination [19,20].…”
Section: Introductionmentioning
confidence: 99%